A nontoxic biocompatible nanocomposite comprising black phosphorus with Au–γ-Fe2O3 nanoparticles. Issue 27 (23rd April 2020) - Naskar, Atanu; Kim, Semi; Kim, Kwang-sun
Abstract : Synthesis of the Au–γ-Fe2 O3 –BP nanocomposite and its activity. Abstract : Black phosphorus (BP) has emerged as the latest 2D material within the post-graphene scenario, which can be used for various biomedical applications. In this study, we reported a promising nanocomposite material, which could be assembled with Au nanoparticles and γ-Fe2 O3 nanoparticles on BP nanosheets (AIB), and studied its biocompatibility that promises to be useful for various biomedical applications. The synthesis of the Au–γ-Fe2 O3 nanomaterial was attained through low-temperature solution synthesis and the exfoliation of BP nanosheets was performed through a liquid ultrasonication process. The individual components were then composited by ultrasonication and stirring. X-ray diffraction and transmission electron microscopic analyses confirmed the existence of Au and γ-Fe2 O3 nanoparticles (NPs) assembled over BP nanosheets. Moreover, the surface chemical composition and valence state of the elements present in the AIB nanocomposite were evaluated with the help of an X-ray photoelectron spectroscopy study. The AIB nanocomposite exhibited excellent biocompatibility with HCT-15 cells after evaluating through WST assay. Therefore, the excellent biocompatible nature of this BP nanocomposite could be beneficial for various potential biomedical applications.